A Critical Evaluation of the Thinking Frames Approach as a Teaching Strategy for Multidimensional Conceptual Change in the Science Classroom - McLure, Felicity Isabel (Curtin University, 2018)
This study investigated how a multi-dimensional conceptual change strategy, called the Thinking Frames Approach (TFA), supported students’ learning. The study was conducted in Grades 8-10 science classes over a two-year period. Results showed that students improved their conceptual understanding and written explanations in many science topics. Students’ interest and self-efficacy in science were also positively influenced. TFA support provided to the teacher in guiding students to go through multi-dimensional conceptual change is also discussed.